The validity and reliability study of the University of California, Los Angeles Scleroderma Clinical Trial Consortium Gastrointestinal Tract (UCLA SCTC GIT) 2.0 questionnaire for the Turkish society - Yaşar Murat Taş; Gözde Derviş Hakim; Pembe Keskinoğlu; Gökçe Kenar; Handan Yarkan; Berrin Zengin; Gerçek Can; Fatoş Önen; Nurullah Akkoç; Merih Birlik; Mesut Akarsu (Turkish Journal of Gastroenterology, 2019)
Background/Aims: To translate the University of California, Los Angeles Scleroderma Clinical Trial Consortium Gastrointestinal Tract (UCLA SCTC GIT) 2.0 questionnaire from English to Turkish and to validate it. Materials and Methods: UCLA SCTC GIT 2.0 was translated into Turkish using the translation-retranslation method. The available Turkish GIT 2.0 and the Short Form 36 (SF-36) were administered to 97 Turkish-speaking patients with systemic sclerosis (Ssc). Internal consistency reliability and structural validity were assessed by analyzing the correlations between the UCLA SCTC GIT 2.0 and the SF-36 scales. Internal consistency was determined by calculating Cronbach’s alpha. For evaluation of reliability, the questionnaire scale was repeatedly applied to a subgroup of patients with a 2-week interval, and the intraclass correlation coefficient (ICC) was calculated. The Spearman’s correlation coefficients between the GIT and the SF-36 scores were calculated. Results: A group of 97 patients with Ssc with a mean age of 55.37±11.35 years and a female predominance (87.6%) were included in the study. The Cronbach’s alpha value for the UCLA SCTC GIT 2.0 scale was 0.894. ICC was 0.821 (p=0.000). The scale showed acceptable reliability, with the exception of the diarrhea subscale (alpha=0.356). There was a moderate correlation between the total GIT score and the Short Form 36 (SF-36) subscales. All of the items in the scale were included in the validity analysis owing to their reliability. Conclusion: The Turkish GIT 2.0 scale showed good internal consistency, high reliability, and an acceptable validity. Cite this article as: Taş YM, Derviş Hakim G, Keskinoğlu P, et al. The validity and reliability study of the University of California, Los Angeles Scleroderma Clinical Trial Consortium Gastrointestinal Tract (UCLA SCTC GIT) 2.0 questionnaire for the Turkish society. Turk J Gastroenterol 2019; 30(3): 234-41.